2006
DOI: 10.1073/pnas.0602620103
|View full text |Cite
|
Sign up to set email alerts
|

The chemokine SDF-1/CXCL12 modulates the firing pattern of vasopressin neurons and counteracts induced vasopressin release through CXCR4

Abstract: Chemokines play a key role in inflammation. They are expressed not only in neuroinflammatory conditions, but also constitutively by different cell types, including neurons in the normal brain, suggesting that they may act as modulators of neuronal functions. Here, we investigated a possible neuroendocrine role of the chemokine stromal cell-derived factor 1 (SDF-1)͞CXCL12. We demonstrated the colocalization of SDF-1 and its receptor CXCR4 with arginine vasopressin (AVP) in the magnocellular neurons of the supra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0
2

Year Published

2007
2007
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 34 publications
9
65
0
2
Order By: Relevance
“…These data suggest that chemokines may represent a new class of neuromodulatory peptides that may be involved notably in the autocrine neuroendocrine control of AVP neurons ( Fig. 4; Callewaere et al 2006).…”
Section: Acute Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…These data suggest that chemokines may represent a new class of neuromodulatory peptides that may be involved notably in the autocrine neuroendocrine control of AVP neurons ( Fig. 4; Callewaere et al 2006).…”
Section: Acute Stimulationmentioning
confidence: 99%
“…By means of dual fluorescent immunohistochemistry (Banisadr et al 2003, Callewaere et al 2006, we first demonstrated the co-localization of SDF-1/CXCL12 and its receptor CXCR4 with AVP neurons in the magnocellular neurons of the SON and PVN hypothalamic nuclei and on AVP projections in the median eminence (Fig. 1) to the neurohypophysis (Callewaere et al 2006). Electrophysiological recordings of SON neurons clearly demonstrate that SDF-1/CXCL12 through its receptor CXCR4 affects the electrical activity of AVP neurons.…”
Section: Chemokines and Water Balancementioning
confidence: 99%
See 1 more Smart Citation
“…SDF-1a modulates the activity of vasopressinergic neurons recorded in the rat supraoptic and paraventricular nucleus slices through CXCR4, resulting in changes in the AVP release (Callewaere et al 2006). SDF-1a can blunt the autoregulation of AVP release in vitro and counteract angiotensin II-induced plasma AVP release in vivo.…”
Section: Effects On Neuronal Activity and Neurotransmitter Releasementioning
confidence: 99%
“…By blocking CXCR4, antagonist human Immunodeficiency virus (HIV)-1 gp120 inhibits the long-term potentiation (LTP) in the CA1 region of rat hippocampus through indirect release of gamma-aminobutyric acid type A (GABAA) while no effects were observed on basal synaptic transmission (Dong J and Xiong H, 2006). CXCL12 affects the electrical activity of arginine vasopressin (AVP) neurons, resulting in changes in AVP release (Callewaere C et al, 2006). Chemokines and gp120 have been suggested to facilitate pain pathways via direct actions on chemokine receptors expressed by nociceptive neurons (Oh SB et al, 2001).…”
Section: Neuromodulationmentioning
confidence: 99%